METHODS AND COMPOSITIONS FOR TREATING DISORDERS WITH ORAL SYSTEMICALLY BIOAVAILABLE BUTYRATE CONJUGATES - CAO, Shijie; BUDINA, Erica; WATKINS, Elyse; RACZY, Michal; HUBBELL, Jeffrey (2025)
Described herein are novel methods of treating disorders using oral, systemically bioavailable forms of butyrate. Aspects of the disclosure relate to a method for treating a disorder in a subject comprising administering the oral, systemically bioavailable composition to the subject, wherein the disorder is selected from inflammatory bowel disease (IBD), multiple sclerosis (MS), a neuroinflammatory condition, food allergies, rheumatoid arthritis (RA), asthma, celiac disease, non-alcoholic steatohepatitis (NASH), diabetes, Alzheimer's disease (AD), inflammaging, beta-hemoglobinopathies, vascular inflammatory conditions, atopic dermatitis and psoriasis, pulmonary fibrosis, and systemic sclerosis.